2002
DOI: 10.1063/1.1499991
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between grain size and optical properties in zinc oxide thin films

Abstract: Nanoantenna-like properties of sea-urchin shaped ZnO as a nanolight filter Appl. Phys. Lett. 101, 133101 (2012) Leaky mode analysis of luminescent thin films: The case of ZnO on sapphire J. Appl. Phys. 112, 063112 (2012) ZnO/ZnSxSe1−x core/shell nanowire arrays as photoelectrodes with efficient visible light absorption Appl. Phys. Lett. 101, 073105 (2012) Study of the photoluminescence emission line at 3.33eV in ZnO films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 11 publications
1
79
0
Order By: Relevance
“…The decay time remains constant, pointing to a uniform distribution of dopant in the particles of various sizes. Matsumoto et al [10] reported the influence of particle size on the photoluminescence of undoped ZnO. In addition, they not only observed an increase in luminescence intensity but also an increase in the decay times.…”
Section: Alternate Low Temperature Synthesismentioning
confidence: 91%
“…The decay time remains constant, pointing to a uniform distribution of dopant in the particles of various sizes. Matsumoto et al [10] reported the influence of particle size on the photoluminescence of undoped ZnO. In addition, they not only observed an increase in luminescence intensity but also an increase in the decay times.…”
Section: Alternate Low Temperature Synthesismentioning
confidence: 91%
“…larger, and hence smaller grains will have more nonradiative relaxation centers from the surface states. 33,34 The increased nonradiative relaxation results in the noticeable decrease in the UV excitonic emission intensity. Thus, the optical quality of the samples increases with the increase in grain size.…”
Section: -3mentioning
confidence: 99%
“…9 A major asset of ZnO is that its Photoluminescence (PL) spectra consist of two emission components: a narrow UltraViolet (UV) peak at around 380 nm, which is correlated with the near band-edge (NBE) exciton emission, 10 and a broad visible (VIS) peak spanning from 450 to 750 nm, which is associated with deep level emission (DLE) from intrinsic and extrinsic defects. [11][12][13][14] The fabrication of high-quality ZnO films with strong UV or VIS emission is a challenging task; a high-temperature deposition or/and a post-deposition annealing scheme is usually required 15,16 with thermal annealing 17 and rapid thermal annealing, 18 which however are not compatible with temperature sensitive underlayers, such as thin metal layers. Consequently, laser annealing 19,20 (LA), being a cold process, is a favourable alternative for processing such structures.…”
Section: Introductionmentioning
confidence: 99%